SIMULASI PENENTUAN LOKASI GANGGUAN SATU FASA PADA JARINGAN TEGANGAN MENENGAH 20 KV BERBASIS ARDUINO MEGA 2560 DILENGKAPI DENGAN MONITORING MELALUI VTSCADA - Ashifa, Danu Nur; Subari, Arkhan (Vocational School Diponegoro University, 2019)
Danu Nur Ashifa, Arkhan Subari in this paper explain that in a distribution network of 20 KV, short circuit interference often occurs. Short circuit interference will produce a fault current that is felt by protection equipment. Each fault current will differ depending on the distance of the interference. Determining the distance of interference can not be displayed in SCADA, SCADA will only display the amount of interference and which equipment works. Determination of distance is carried out after analysis by the officer. Based on this matter the compiler makes a simulation tool where the tool can monitor the location of the disturbance from the nearest protective equipment that feels a single phase short circuit interference. The simulation tool consists of Arduino Mega 2560 which functions as a control center. The input used is a potentiometer as a simulator of the impedance magnitude that occurs during a single phase short circuit where the potentiometer will provide input in the form of a signal. And Omron LY2N relay which functions as protection equipment. After the experiment, the results obtained are that the tool can determine the location of interference from the nearest protection equipment based on changes in the bits read by Arduino. The larger the bits read by Arduino, the more distant the interference occurs from the protection equipment. 125 bits will produce an Arduino impedance calculation of 2.6 ohms so that the fault location is 0 km from PMT while 1023 bits will produce an impedance calculation of 21.30 ohms so that the fault location is 4.5 km from SSO.